Answer: The correct option is (D) 196608.
Step-by-step explanation: We are given to find the 9th term of the following sequence :
3, -12, 48, -192, . . .
Let a(n) denote the n-th term of the given sequence.
Then, a(1) = 3, a(2) = -12, a(3) = 48, a(4) = -192, . . .
We see that
![(a(2))/(a(1))=(-12)/(3)=-4,\\\\\\(a(3))/(a(2))=(48)/(-12)=-4,\\\\\\(a(4))/(a(3))=(-192)/(48)=-4,~~.~~.~~.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2iu5vyj03cqmxkcwqug1j9003ye1b31jjs.png)
So, we get
![(a(2))/(a(1))=(a(3))/(a(2))=(a(4))/(a(3))=~~.~~.~~.~~=-4.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m5c4g7acyud3ljyhbm4yvfnsf34qpufks3.png)
That is, the given sequence is a GEOMETRIC one with first term a = 3 and common ratio d= -4.
We know that
the n-th term of an geometric sequence with first term a and common ratio r is given by
![a(n)=ar^(n-1).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f5ensy17fhdhs1bsvmne8wnocvq1a6rc55.png)
Therefore, the 9th term of the given sequence is
![a(9)=ar^(9-1)=3*(-4)^8=3* 65536=196608.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nbhzul2rnvumcz61nrer8p5zjw7602h6k6.png)
Thus, the 9th term of the given sequence is 196608.
Option (D) is CORRECT.